STRATEGI PENGEMBANGAN SISTEM WAREHOUSE UNTUK MENGATASI TANTANGAN INDUSTRI - Pujo Iswahyudi; Muhammad Khairil Ihsan, Paduloh (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research aims to explore effective warehouse system development strategies to address complex industry challenges. Based on literature analysis and case studies, this research identifies several key strategies, such as building a data-driven culture, defining clear goals and needs, selecting the right architecture and technology, implementing a strong data governance framework, and investing in employee training and education. The research also discusses the benefits of implementing an effective data warehouse strategy, including better decision-making, increased operational efficiency, improved customer satisfaction, and gaining a competitive advantage. In conclusion, this research highlights the importance of developing an effective warehouse system in facing modern industry challenges and achieving the benefits of data-driven decision-making for long-term success in today's digital age